SYSTEM SET UP FOR InxGa1-xN PHOTOLUMINESCENCE MEASUREMENT - PUTRI WIBOWO (NIM : 10208059); Pembimbing : Pepen Arifin Ph.D, ANGGITA
Photoluminescence is an optical characterization technique onto a semiconductor material to provide information about the bandgap energy and properties of the material. Photoluminescence experiments include literature study about the luminescence process on semiconductor materials, the experiment device system setup, as well as data processing and analysis of the experiment results. Photoluminescence system setup was initiated by setting the whole system to find a suitable and precision configuration. Photoluminescence system that has been assembled, was then tested the feasibility of the Photoluminsecence using Mercury (Hg) lamp to get the appropriate light spectrum as in reference. The light source in the setup that has been proven, was replaced with InxGa1-xN samples which had been grown by PA-MOCVD method, and was excited by 532nm green laser. From the results of measurements of InxGa1-xN with In concentration of 10%, 20%, and 40%, the spectrum line in the yellow areas around 570nm was found, which indicates the existence of defects in all three samples above. However, it needs a higher energy laser to get the whole spectra of InxGa1-xN samples that have a value of 0.7 ~ 3.4eV energy band as in references.